URBAN PLANNING PERSPECTIVES OF THE POTENTIAL OF RESORT DEVELOPMENT IN THE SERGEEVKA SETTLEMENT WITH TRAFFIC IMPROVEMENT (Advances in Civil and Architectural Engineering, 2021)
The Sergeevka resort is the largest climatic-balneal-mud resort in the south of Odessa region. This article presents an overview of the current state of the resort and an analysis of its transport-planning scheme. In addition, suggestions on the resort’s availability and improvement of its functioning are provided through reconstruction of the resort’s external (in particular with Odessa) and internal transport links. Based on the city-planning analysis of the existing access roads to the resort and within its territory, the study presents a concept of the organization of the transport scheme. Its basic arrangements will provide the opportunity for the development of the resort by contributing to the influx of vacationers and investments and creation of new workplaces.